If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -37 = 7x + 27 Reorder the terms: -37 + 11x = 7x + 27 Reorder the terms: -37 + 11x = 27 + 7x Solving -37 + 11x = 27 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -37 + 11x + -7x = 27 + 7x + -7x Combine like terms: 11x + -7x = 4x -37 + 4x = 27 + 7x + -7x Combine like terms: 7x + -7x = 0 -37 + 4x = 27 + 0 -37 + 4x = 27 Add '37' to each side of the equation. -37 + 37 + 4x = 27 + 37 Combine like terms: -37 + 37 = 0 0 + 4x = 27 + 37 4x = 27 + 37 Combine like terms: 27 + 37 = 64 4x = 64 Divide each side by '4'. x = 16 Simplifying x = 16
| 10x-7+2x+3=12+4x+6-3x | | x^4-4x^3+3x^2+4x+4=0 | | 75=0.5h(50) | | 75=2h(50) | | 2a*3bc*5d= | | 15=3+7+c | | 4x*7y= | | 84+x= | | 9p+8q-2p+7q= | | 27x^2-27x-12=0 | | y^2-12x-45=0 | | 10x-5x+4y+7y= | | 2(x-1)=4x+4 | | 4ab+6a-b+5a-ab= | | -4x+3=2+4x | | 17x^3-13x-4x=0 | | 3tgx+5ctgx-8=0 | | y^2+5zy+4z^2=0 | | 7(g+10)+3(2g-1)=5 | | 8x^2-xy-7y^2=0 | | (4x-9)(2x+2)=0 | | 5(2v-4)-2(3v+2)=-4 | | -2x+1=-5x+7 | | -4x-8=6x+22 | | 2x-(3x+5)=15+6(x-1) | | 6(b+2)+3(b+1)=25 | | -3x+3=2x+1 | | -2(t-5)-(t+6)=8 | | 1x+1=2+6x | | 4(e-3)-2(e+4)=6 | | lx-1l-2=0 | | 18-9x=8-x |